2010
DOI: 10.1111/j.1745-4549.2009.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Eggplant Slices in Thin Layers at Different Air Temperatures

Abstract: The effect of water‐blanching treatment and air temperature on drying kinetics of eggplant slices were investigated at air temperatures (50, 60, 70 and 80C). Both the blanching and air temperature influenced the drying time of eggplant slices. Moisture ratios were fitted to 11 different mathematical models using nonlinear regression analysis. The regression results showed that the logarithmic, Wang and Singh, and Midilli et al. models satisfactorily described the drying behavior of eggplant slices with highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
2
22
1
2
Order By: Relevance
“…The results showed that Midilli and Wang & Sing models gave the superior fit to the experimental data compared to other models (Table 3). Similar to our findings, Doymaz (2011) Table 4. The effective diffusivities of zucchini samples varied from 0.58Ö10 −9 to 1.93Ö10 −9 m 2 s −1 .…”
Section: Convective Hot-air Dryingsupporting
confidence: 92%
“…The results showed that Midilli and Wang & Sing models gave the superior fit to the experimental data compared to other models (Table 3). Similar to our findings, Doymaz (2011) Table 4. The effective diffusivities of zucchini samples varied from 0.58Ö10 −9 to 1.93Ö10 −9 m 2 s −1 .…”
Section: Convective Hot-air Dryingsupporting
confidence: 92%
“…A nonlinear estimation package (Curve Expert, Version 1.34) was used to estimate the models coefficients. The correlation coefficient ( R ) and standard error ( SE ) were calculated to adjust the experimental results to the models A desirable fitness is achieved at low SE and high R values, (Doymaz, ).…”
Section: Methodsmentioning
confidence: 99%
“…The most widespread empirical models in literature are those of Newton, Page, Henderson and Pabis, Wang and Singh (Akpinar and Bicer, 2005;Ertekin and Yaldiz, 2004), and were applied to the description of several aspects of drying processes (Khalloufi et al, 2009(Khalloufi et al, , 2010 for many foodstuffs e.g. quince (Koc et al, 2008), eggplant (Doymaz, 2011;Ertekin and Yaldiz, 2004), cherry tomato (Heredia et al, 2007), apricot (Togrul and Pehlivan, 2003), mushroom (Hernando et al, 2008), and black tea (Panchariya et al, 2002).…”
Section: Introductionmentioning
confidence: 99%